THE BED-BY-BED STANDARD OF THE SILURIAN FOR EASTERN SIBERIA - Tesakov I.Yu.; Khromykh V.G.; Berger A.Ya.; Predtechenskii N.N. (My University, 1998)
The bed-by-bed standard of the Silurian for East Siberia is used to correlate stratigraphic sequences all over the Siberian platform and Taimyr. Fossil faunas and floras of the standard are very representative, because the original type sections of the standard consist of deposits accumulated in shallow shelf settings favorable for biota evolution. Consecutive beds of the standard are characterized by distribution parameters (abundance rates and size ranges) of the following fossil groups: algae, stromatoporoids, tabulates, heliolitids, rugose corals, crinoids, gastropods, ostracodes, tentaculitids, bryozoans, conodonts, scolecodonts, bivalves, brachiopods, trilobites, cephalopods, acritarchs, chitinozoans, and graptolites. The biocoenotic analysis is based on data characterizing the taxonomy and relative abundance of fossils in oryctocoenoses, and on the structure of the latter.
Keywords: Silurian; Paleozoic::Silurian; Палеозой::Силурийская